Masks as Transitional Objects - Kater, Aude (O Mundo da Saúde, 2012)
This article focuses on Masks as transitional objects, according to the concept proposed by Winnicott. Other authors such as Bruner, Wallon, Anzieu, and Broustra also bring their principles for supporting an art-therapy approach in relationships with youngsters having social difficulties. The creation of a mask from the mold of the very face of people allows installing a process of reconstruction of identity, supporting itself in the symbolic figure of the “Hero”. In this report, our especial foci are the importance of mediation by adults, intentionality and symbolic action for ressignifying the lived in a positive way.